Weak noncovalent interactions in two positional isomers of acrylonitrile derivatives: inputs from PIXEL energy, Hirshfeld surface and QTAIM analyses - Percino, M. Judith; Udayakumar, Mani; Cerón, Margarita; Pérez-Gutiérrez, Enrique; Venkatesan, Perumal; Thamotharan, Subbiah (Frontiers in Chemistry, 2023)
A single crystal X-ray diffraction analysis was performed on two positional isomers (m-tolyl and p-tolyl) of acrylonitrile derivatives, namely, (Z)-3-(4-(pyridin-2-yl) phenyl)-2-(m-tolyl) acrylonitrile (1) and (Z)-3-(4-(pyridin-2-yl)phenyl)-2-(p-tolyl) acrylonitrile (2). Compound 1 crystallized in the monoclinic P21/n space group with two crystallographically independent molecules. Compound 2 also possesses two crystallographically independent molecules and crystallized in the triclinic P-1 space group. The Hirshfeld surface analysis revealed that, in both isomers, intermolecular H⋅⋅⋅H/C/N contacts contribute significantly to the crystal packing. More than 40% of the contribution arises from intermolecular C–H⋅⋅⋅C(π) contacts. In both compounds, the relative contribution of these contacts is comparable, indicating that the positional isomeric effects are marginal. The structures in which these isomers are arranged in the solid state are very similar, and the lattice energies are also comparable between the isomers. The Coulomb-London-Pauli-PIXEL (CLP-PIXEL) energy analysis identified the energetically significant dimers. The strength of the intra- and intermolecular interactions was evaluated using the quantum theory of atoms in molecules approach. The UV-Vis absorbance in three different solvents (chloroform, ethanol, and ethyl acetate) for isomers 1 and 2 are very similar. This result is in good agreement with the time-dependent density-functional theory (TD-DFT) calculations.